Electromagnetism [2nd ed.] problems with solutions - Pramanik, Ashutosh (New Delhi PHI Leaning, 2009)
The second edition of this book contains 40 new problems over and above the original 440 problems. The additional problems cover the whole range of new topics as introduced in the second edition of the author's main text entitled Electromagnetism: Theory and Applications. What Is NEW in This Edition ? A number of new problems demonstrate the use of Bessel and Legendre functions required for practical solutions to guidance and transmission problems of electromagnetic waves in waveguides and antennae. ? Bessel and Legendre functions have also been introduced in the initial topics on electrostatics and magnetostatics so that the readers would develop familiarity with these important mathematical functions at an earlier stage to be able to solve problems dealing with cylindrical and spherical geometries. ? Some problems in antennae have been solved by using the Hertz vector to show how the use of Hertz vector makes the solving of these problems easier. ? Some problems on transmission lines requiring the use of Bicylindrical coordinate system have also been included. ? A new appendix on Bicylindrical coordinate system has been added. There has been no change in the philosophy of this book. It has been designed to serve as a companion volume to the main text to help students gain a thorough quantitative understanding of EM concepts that are somewhat difficult to learn. The problems included, as a result of the author's long industrial and academic experience, illuminate the concepts developed in the main text. Besides meeting the needs of undergraduate students of electrical enginee
Keywords: Electromagnetism; Electricity